Exploring the Relationship between Attention-Deficit Hyperactivity Disorder (ADHD) and Campus Bullying: Prevalence, Impact, and Intervention Strategies in Primary and Secondary Schools - Yongmei, Hou (Disease and Health Research: New Insights Vol. 8, 2024)
Background: Attention-Deficit Hyperactivity Disorder (ADHD) and campus bullying are common mental and behavioral problems among children and adolescents, which have significant negative impacts on their physical and mental health as well as the normal functioning of primary and secondary schools. Objective: The objective of the study is to understand the prevalence of ADHD and campus bullying in primary and secondary schools, explore their relationship, and analyze intervention approaches for campus bullying related to ADHD. Methods: Literature retrieval was used to review 50 papers in the past 20 years, and the clinical characteristics and prevalence of the two, as well as influencing factors of campus bullying related to students with ADHD in primary and secondary schools, were represented. And then, the impact of ADHD on-campus bullying was analyzed. On this basis, ways were proposed to address the phenomenon of campus bullying related to children and adolescents with ADHD. Results: The incidence of ADHD in foreign countries is 3% to 7%, while in China it is 2.4% to 13%. Forty-six-point nine percent of ADHD children abroad and 50.7% of ADHD children in China are involved in school bullying incidents, Compared to peers with normal development, adolescents with ADHD are more likely to become victims and bullies, influenced by personal traits and risk factors in the environment. Possible intervention approaches include family upbringing, school education, and social intervention. Conclusion: ADHD is closely related to campus bullying in primary and secondary school students. Multi-level comprehensive interventions are needed from family, school, and society to reduce the involvement of children and adolescents with ADHD in school bullying incidents.